2021
DOI: 10.1111/zph.12872
|View full text |Cite
|
Sign up to set email alerts
|

A review of Cyclospora cayetanensis in animals

Abstract: Cyclosporiasis is an emerging disease in humans with a worldwide scope (Chacín-Bonilla, 2017). The disease is typified by watery diarrhoea that can last for weeks or even months, with more severe or prolonged symptoms occurring in young children and immunocompromised populations. Cyclosporiasis is caused by the single-celled parasite, Cyclospora cayetanensis. Humans become infected by ingesting water, food or soil contaminated with C. cayetanensis in its infective (sporulated oocyst) stage (Chacín-Bonilla, 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…These animals and environmental agents, as mentioned in published papers incorporated in this review, and represented in this picture were investigated for Cyclospora oocysts. The presence of Cyclospora oocysts in the animal faeces does not indicate infection and cannot be considered the reservoir of C. cayetanensis; however, Cyclospora oocysts might act as paratenic hosts [14] to disseminate this pathogen to the surroundings where humans can be infected. A biopsy is the only means by which whether the animals are actually infected can be ascertained.…”
Section: Cyclospora Spp In Domestic Animalsmentioning
confidence: 99%
See 2 more Smart Citations
“…These animals and environmental agents, as mentioned in published papers incorporated in this review, and represented in this picture were investigated for Cyclospora oocysts. The presence of Cyclospora oocysts in the animal faeces does not indicate infection and cannot be considered the reservoir of C. cayetanensis; however, Cyclospora oocysts might act as paratenic hosts [14] to disseminate this pathogen to the surroundings where humans can be infected. A biopsy is the only means by which whether the animals are actually infected can be ascertained.…”
Section: Cyclospora Spp In Domestic Animalsmentioning
confidence: 99%
“…Cyclospora oocysts have been identified in monkeys [54,59] and Himalayan goral [76] (Table 3) in Nepal. According to one review [14], some attempts have been successful in infecting oysters, Asian fresh water clams, Swiss albino mice, and guinea pigs through artificial inoculation of C. cayetanensis oocysts. Based on the appearance of oocysts in the faeces, it cannot be concluded that the animals are infected by Cyclospora.…”
Section: Cyclospora Spp In Wild Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cyclospora spp. are protozoan parasites of the phylum Apicomplexa that parasitize many species of mammals with remarkable host specificity [ 1 , 2 , 3 ]. Until recently, Cyclospora cayetanensis was the only species designated within the genus known to infect humans [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Until recently, Cyclospora cayetanensis was the only species designated within the genus known to infect humans [ 4 ]. Several Cyclospora species have been found in other animals [ 3 , 5 ], and two new species have been described recently ( Cyclospora duszynskii and Cyclospora yatesi ) from Eastern moles ( Scalopus aquaticus ) in Arkansas, USA, based on distinct microscopical features of their oocysts [ 6 ].…”
Section: Introductionmentioning
confidence: 99%